MY SAY: The myth about going green - Abd Razak, Dzulkifli (2009)
In my last column, I cited examples of how the UK initiated its green energy programme and the importance of walking the talk. While this may be the case for the UK government, it is not necessarily so for British companies. A case in point: two British companies were found to have exported some 1,400 tonnes of hazardous waste to Brazilian ports. This was confirmed by the country's environmental inspectorate recently. The suspected illegal shipments are said to contain toxic waste from hospitals and elsewhere, including syringes, condoms and nappies. A Brazilian company said to be acting as an intermediary in the illegal activity was also named.